2020
DOI: 10.3389/fnins.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Individual Differences in Motor Behavior by Intrinsic Functional Connectivity and Corticospinal Excitability

Abstract: Motor performance varies substantially between individuals. This variance is rooted in individuals' innate motor abilities, and should thus have a neural signature underlying these differences in behavior. Could these individual differences be detectable with neural measurements acquired at rest? Here, we tested the hypothesis that motor performance can be predicted by resting motor-system functional connectivity and motor-evoked-potentials (MEPs) induced by non-invasive brain stimulation. Twenty healthy right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…It has been hypothesized that RSN originate from spontaneous cognition taking place during conscious wakefulness (also known as mind-wandering) (Gonzalez-Castillo et al, 2021). This hypothesis is compatible with the small increase in metabolism seen during effortful tasks, since spontaneous brain activity would already reflect ongoing cognitive processing; furthermore, it is also consistent with studies showing that resting state activity can be used to decode mental states (Richiardi et al, 2011;Gonzalez-Castillo et al, 2015), as well as to predict performance in motor and perceptual tasks (Boly et al, 2007;Hesselmann et al, 2008;Kannurpatti et al, 2012;Sadaghiani et al, 2015;Herszage et al, 2020). A seminal study published by Smith and colleagues demonstrated a direct correspondence between the spatial configuration of RSN and task-evoked activity patterns, obtained by applying ICA to a large database of brain activation maps (www.brainmap.org) (Smith et al, 2009).…”
Section: Introductionsupporting
confidence: 81%
“…It has been hypothesized that RSN originate from spontaneous cognition taking place during conscious wakefulness (also known as mind-wandering) (Gonzalez-Castillo et al, 2021). This hypothesis is compatible with the small increase in metabolism seen during effortful tasks, since spontaneous brain activity would already reflect ongoing cognitive processing; furthermore, it is also consistent with studies showing that resting state activity can be used to decode mental states (Richiardi et al, 2011;Gonzalez-Castillo et al, 2015), as well as to predict performance in motor and perceptual tasks (Boly et al, 2007;Hesselmann et al, 2008;Kannurpatti et al, 2012;Sadaghiani et al, 2015;Herszage et al, 2020). A seminal study published by Smith and colleagues demonstrated a direct correspondence between the spatial configuration of RSN and task-evoked activity patterns, obtained by applying ICA to a large database of brain activation maps (www.brainmap.org) (Smith et al, 2009).…”
Section: Introductionsupporting
confidence: 81%
“…There have been several previous attempts to quantify neurophysiological markers of motor learning and performance (Baetu et al, 2015;Andreska et al, 2020;Herszage et al, 2020). Such attempts have included resting-state electroencephalography (EEG) activity, which has been shown to pre-dict visuomotor performance with the rotary pursuit task (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that regions including primary motor cortex and supplementary motor area (SMA) are critical for the formation of motor plans, including the relay of kinematic transformation to the task specific effector [72][73][74][75][76] . Increased resting state FC between the cerebellum and both the primary motor cortex and SMA is associated with learning a finger-opposition sequence task 77,78 . Additionally, our previous work showed that high-intensity interval exercise led to a release of cerebellar inhibition 79 .…”
Section: Exercise and Motor Skill Learningmentioning
confidence: 99%